INPPO Actions and Recognition as a Driving Force for Progress in Plant Proteomics: Change of Guard, INPPO Update, and Upcoming Activities. Issue 21 (12th November 2013) - Agrawal, Ganesh Kumar; Job, Dominique; Kieselbach, Thomas; Barkla, Bronwyn J.; Chen, Sixue; Deswal, Renu; Lüthje, Sabine; Amalraj, Ramesh Sundar; Tanou, Georgia; Ndimba, Bongani Kaiser; Cramer, Rainer; Weckwerth, Wolfram; et al.
Abstract : The International Plant Proteomics Organization (INPPO) is a non‐profit organization whose members are scientists involved or interested in plant proteomics. Since the publication of the first INPPO highlights in 2012, continued progress on many of the organization's mandates/goals has been achieved. Two major events are emphasized in this second INPPO highlights. First, the change of guard at the top, passing of the baton from Dominique Job, INPPO founding President to Ganesh Kumar Agrawal as the incoming President. Ganesh K. Agrawal, along with Dominique Job and Randeep Rakwal initiated the INPPO. Second, the most recent INPPO achievements and future targets, mainly the organization of first the INPPO World Congress in 2014, tentatively planned for Hamburg (Germany), are mentioned.